1990
DOI: 10.1161/01.cir.82.5.1790
|View full text |Cite
|
Sign up to set email alerts
|

Vascular reactivity after balloon angioplasty in an atherosclerotic rabbit.

Abstract: Alterations in vessel wall reactivity (VR) at or adjacent to the dilation site after balloon angioplasty (BA) may vary according to the inflation protocol and the time after angioplasty and may influence outcome. In 64 atherosclerotic rabbit femoral arteries, we evaluated VR after BA with intravenous ergonovine (ERGO) (40 ,ug/min for 5 minutes) and intra-arterial nitroglycerin (NTG) (2,500 ,ug single bolus)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Details of this experimental model have been published previously. [17][18][19] Induction of Focal Atherosclerosis Fifty-nine male New Zealand White rabbits (weight, 4.0±0.4 kg) were anesthetized with ketamine (50 mg/kg i.m.) and xylocaine (5 mg/kg i.m.).…”
Section: Methodsmentioning
confidence: 99%
“…Details of this experimental model have been published previously. [17][18][19] Induction of Focal Atherosclerosis Fifty-nine male New Zealand White rabbits (weight, 4.0±0.4 kg) were anesthetized with ketamine (50 mg/kg i.m.) and xylocaine (5 mg/kg i.m.).…”
Section: Methodsmentioning
confidence: 99%
“…This finding is consistent with the presence of vasospasm at the angioplasty site in the fluoxetine-treated rabbits and would appear to be in conflict with data published earlier from our laboratory when we reported that vasospasm does not occur at the angioplasty site after angioplasty. 23 In this study, a balloon matched to the lumen size was used. Histologically, there was less medial damage than reported previously, and thus, the vessel was presumably able to react to the intense vasospastic stimulus that was present in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Often these processes occur in concert, and the individual effects of each are difficult to separate. 118 Vasospasm after angioplasty has been identified in both animals 19 " 23 and patients. 24 Its contribution to acute vessel closure is suggested by reversal of the acute occlusion in some cases with vasodilators.…”
mentioning
confidence: 99%
“…In our anesthetized rabbits, it is likely that the studied vessels are maximally dilated at baseline, as demonstrated by their lack of further dilatation to infused nitrogrycerin. 26 Thus, any vasodilatory effect of lowdose serotonin on normal vessels may be masked. Similarly, others have reported that the S 2 -mediated contractile effects of serotonin may predominate in vivo, 27 and serotonin-induced endothelium-dependent relaxation may not be apparent unless unmasked by an S 2 -receptor antagonist.…”
Section: Histology (Figure 9)mentioning
confidence: 99%
“…35 We have shown previously in this model that dilatation to 10 arm with an appropriately sized balloon causes moderate degrees of medial necrosis and patchy areas of acellularity in the treated areas 32 and that this may render the dilatation site unresponsive to ergonovineinduced vasoconstriction. 26 Of note, treated sites can regain some responsiveness to vasoconstrictors with time, 26 particularly to serotonin. 36 Others have suggested that treated sites do retain the ability to vasoconstrict when treated with appropriately sized balloons at relatively low inflation pressures.…”
mentioning
confidence: 99%